2008 IEEE MTT-S International Microwave Symposium Digest 2008
DOI: 10.1109/mwsym.2008.4632948
|View full text |Cite
|
Sign up to set email alerts
|

A reconfigurable MEMS-less CMOS tuner for software defined radio

Abstract: -Design, simulation and measurement of a reconfigurable CMOS RF tuner that can be utilized in the RF front-end of a software defined radio are presented. 0.13µm high Q CMOS varactors controlled by a 22bit shift register are placed periodically on a low loss Coplanar Waveguide (CPW) transmission line to form a 4-11GHz reconfigurable tuner. The monolithic tuner does not use any MEMS devices to achieve the reconfigurability.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 8 publications
0
7
0
Order By: Relevance
“…In [6][7], a CPW line is broken down into twenty two tunable sections using CMOS varactors or twenty sections using CMOS switch-capacitor pairs. The overall number of tunable impedance points on the Smith impedance chart are extremely high (2 20 to 2 22 ), and far beyond the impedance points necessary for a practical tuner.…”
Section: Tuner Designmentioning
confidence: 99%
See 2 more Smart Citations
“…In [6][7], a CPW line is broken down into twenty two tunable sections using CMOS varactors or twenty sections using CMOS switch-capacitor pairs. The overall number of tunable impedance points on the Smith impedance chart are extremely high (2 20 to 2 22 ), and far beyond the impedance points necessary for a practical tuner.…”
Section: Tuner Designmentioning
confidence: 99%
“…Reconfigurable tuners have also been demonstrated [5][6][7] and not only find applications in reconfigurable transceivers, but can also be utilized as characterization modules for RF devices and circuits. As a variable impedance matching network at the input of a low noise amplifier, a reconfigurable tuner can provide optimum source impedance for minimum noise figure, maximum gain, or maximum linearity at multiple operating frequency bands.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These floating metal strips isolate the CPW structure from the Si substrate, effectively removing the dielectric losses associated with the Si substrate. This method enables us to obtain loss reduction of around 0.6dB/mm at 10GHz [4].…”
Section: Transmission Linementioning
confidence: 99%
“…An integrated dualband tri-mode CDMA IF receiver with programmable channel-match filter is introduced in [3]. In [4] the authors have reported a field programmable fully integrated CMOS impedance tuner for applications in RF front end of software defined radios.…”
Section: Introductionmentioning
confidence: 99%